Assessment of the need for palliative care in patients with heart failure depending on body composition - V. I. Shevtsova; A. A. Pashkova; O. N. Krasnorutskaya (Российский кардиологический журнал)
Aim. To assess the need for palliative care (PC) in patients with heart failure (HF) depending on body composition.Material and methods. The study involved 298 people (115 men and 183 women, mean age — 61 [53;69] years), who were divided into 5 groups depending on body composition — obesity and sarcopenia. Left ventricular ejection fraction, N-terminal pro-brain natriuretic peptide (NT-proBNP) and galectin-3 markers were determined. Kaplan-Meier analysis was performed to assess survival, while Cox regression — the influence of factors.Results. The maximum values of the time of need for PC are characteristic of patients without body composition disorders, and the minimum ones are for patients with sarcopenic obesity. According to Cox regression, a significant increase in hazard ratio for PC indications occurrence was revealed as 22,9 times (p<0,001) with an increase in muscle mass index to body mass index ratio (MMI/BMI) by 1; 1,99 times (p<0,001) with an increase in functional class by 1; 1-1,02 times (p=0,002) with an increase in the galectin level by 1 ng/mL; 0,96 times (p<0,001) with a decrease in the Barthel index by 1; and 3,71 times (p<0,001) in the presence of sarcopenia.Conclusion. The body composition of patients with HF affects the functional activity of the patient, and therefore the need for PC in patients.